Historical–Geopolitical Contexts and the Transformation of Chinese Foreign Policy. (26th August 2019) - Flint, Colin; Xiaotong, Zhang
Abstract: In the past few years, China has made dramatic foreign policy decisions that have changed both the global landscape and the behaviour of other states. To understand fully the possibilities and limitations of China's foreign policy, it is important to see its occurrences within geopolitical contexts. The main argument of this article is that geopolitical context must be theorised in order to understand the decisions of states. We define a political geography perspective within a world-systems analysis that creates a Space–Time matrix of context based on the core–periphery hierarchy of the capitalist world economy and economic and hegemonic cycles. Inspired by Chinese scholars and policymakers' periodisations of Chinese diplomacy, we develop a new periodisation of Chinese diplomatic cycles from 1840 to 2039. Using this new periodisation of Chinese diplomacy, we situate the changing nature of Chinese foreign policy within our Space–Time matrix. We then evaluate the possibilities and challenges of China's current foreign policy, with emphasis on the Belt and Road Initiative, by illustrating features of the contemporary geopolitical context. Finally, we discuss the implications of this for contemporary Chinese foreign policy.